The effects of thiamethoxam on coffee seedling morphophysiology and Neotropical leaf miner (Leucoptera coffeella) infestations. Issue 6 (16th April 2022) - Leite, Suzany A; Guedes, Raul Narciso C; da Costa, Daniela R; Colmenarez, Yelitza C; Matsumoto, Sylvana N; dos Santos, Mateus P; Coelho, Beatriz S; Moreira, Aldenise A; Castellani, Maria A
Abstract: BACKGROUND: Coffee ( Coffea arabica L.) is one of the main commodities produced in Brazil. Insecticides like the (systemic) neonicotinoid thiamethoxam are widely used to suppress pest populations during coffee production, in particular the Neotropical leaf miner ( Leucoptera coffeella Guérin‐Mèneville & Perrottet, 1842) (Lepidoptera: Lyonetiidae). In addition to its efficacy against this pest species, thiamethoxam is also thought to be a bioactivator of plant metabolism, but has not yet been tested for such activity. Thus, the objectives of the present study were (1) to assess the concentration‐response effects of thiamethoxam on the vegetative vigor of coffee seedlings ( C. arabica 'Catuaí 144' cultivar) at different concentrations [2, 20, 40, 80 and 200 mg active ingredient (a.i.) kg −1 ] applied via soil drenching and (2) to evaluate if the plant response interferes with the effectiveness of thiamethoxam in controlling leaf miner populations. The morphophysiological traits of the coffee seedlings were evaluated 20, 40, 60 and 80 days after application, and leaf miner infestations were recorded starting 20 days after the insecticide application with the releasing of adults, and every 20 days afterwards. RESULTS: The results indicated that thiamethoxam has a deleterious effect on the morphophysiological traits of the plants compromising their development with increase in concentrations. However, leaf area exhibited a different pattern with a peak at 50 mg a.i. kg −1 consistent with thiamethoxam‐induced hormesis (i.e. biphasic response with stimulatory effect at sublethal range of a toxic substance at the higher concentration). Nonetheless, such bioactivator effect did not affect thiamethoxan effectiveness against the leaf miner even at the lowest concentration tested. CONCLUSION: Thiamethoxan exhibited bioactivation effect on leaf at low concentration, but without compromising efficacy against leaf miner populations. Therefore, its proposed metabolism‐boosting properties may encourage the unnecessary use of this insecticide, potentially leading to higher selection for insecticide resistance and an eventual decline in its effectiveness against the Neotropical leaf miner. © 2022 Society of Chemical Industry. Abstract : Thiamethoxam has a deleterious effect on plant morphophysiological traits, except for leaf area. Leaf area exhibits a response pattern consistent with thiamethoxam‐induced hormesis, but with doubtful carry on (bioactivator) effects, although effective against the leaf miner even at the lowest concentration tested.